2021
DOI: 10.1080/15287394.2021.1925608
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish irritant responses to wildland fire-related biomass smoke are influenced by fuel type, combustion phase, and byproduct chemistry

Abstract: submitted to the faculty of the University of North Carolina at Chapel Hill in partial fulfillment of the requirements for the degree of Master of Science in the Curriculum in Toxicology and Environmental Medicine in the School of Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…inhalation in humans vs. immersion dosing in zebrafish - are a challenge to reconcile, the zebrafish model may be used to screen for the potential to elicit mammalian toxicity. Importantly, potency determinations derived from irritant locomotor responses to wildland fire-related PM in zebrafish ( Martin et al, 2021 ) were consistent with separate assessments of the same PM samples in mouse pulmonary toxicity studies that measured pulmonary neutrophil influx ( Kim et al, 2019 ).…”
Section: Danio Reriomentioning
confidence: 52%
See 2 more Smart Citations
“…inhalation in humans vs. immersion dosing in zebrafish - are a challenge to reconcile, the zebrafish model may be used to screen for the potential to elicit mammalian toxicity. Importantly, potency determinations derived from irritant locomotor responses to wildland fire-related PM in zebrafish ( Martin et al, 2021 ) were consistent with separate assessments of the same PM samples in mouse pulmonary toxicity studies that measured pulmonary neutrophil influx ( Kim et al, 2019 ).…”
Section: Danio Reriomentioning
confidence: 52%
“…Zebrafish studies have been useful in identifying the relative toxicity of various PM sources. For example, we previously reported ( Martin et al, 2021 ) that pine biomass induced a stronger irritant response in a locomotor assay at a given concentration than other wildlandfire-related PMs, including eucalyptus, pine needles, red oak, and peat samples. Also, we found that irritant responses significantly correlated with PAH content, but not with organic carbon or methoxyphenols ( Martin et al, 2021 ).…”
Section: Danio Reriomentioning
confidence: 99%
See 1 more Smart Citation
“…This study's findings parallel previous data showing that combustion conditions can greatly impact resulting exposure chemistries and biological responses associated with wildfires. 10,19,42 Transcriptomic Similarity Scoring Informs Biomass Smoke Exposure Groupings. Transcriptomic similarity scoring was employed to identify groups of wildfire-relevant exposures that induce similar responses in the mouse lung at the transcriptome level.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This finding may differ when evaluating exposures that are similar on an emission-factor basis, based on the amount of PM produced per kilogram of fuel burned. For example, a recent zebrafish study found that smoldering smoke condensates caused greater irritant responses in comparison to flaming smoke condensates, when exposures were normalized on an emission factor basis . Additional comparative groups could also be included, for instance, if clean particle exposures existed for the evaluation of woodsmoke conditions, as is done in nanoparticle research .…”
Section: Results and Discussionmentioning
confidence: 99%